The Most Deeply Conserved Noncoding Sequences in Plants Serve Similar Functions to Those in Vertebrates Despite Large Differences in Evolutionary Rates. Issue 3 (28th March 2014) - Burgess, Diane; Freeling, Michael
Abstract : Noncoding sequences conserved over long evolutionary distances can be used to identify DNA regions functioning in gene regulation. This report identifies a set of 211 conserved noncoding sequences found throughout eudicots, a subset of which are found in all flowering plants. These deeply conserved sequences are much shorter than their vertebrate counterparts, yet serve similar functions. Abstract: In vertebrates, conserved noncoding elements (CNEs ) are functionally constrained sequences that can show striking conservation over >400 million years of evolutionary distance and frequently are located megabases away from target developmental genes. Conserved noncoding sequences (CNSs ) in plants are much shorter, and it has been difficult to detect conservation among distantly related genomes. In this article, we show not only that CNS sequences can be detected throughout the eudicot clade of flowering plants, but also that a subset of 37 CNSs can be found in all flowering plants (diverging ∼170 million years ago). These CNSs are functionally similar to vertebrate CNEs, being highly associated with transcription factor and development genes and enriched in transcription factor binding sites. Some of the most highly conserved sequences occur in genes encoding RNA binding proteins, particularly the RNA splicing–associated SR genes. Differences in sequence conservation between plants and animals are likely to reflect differences in the biology of the organisms, with plants being much more able to tolerate genomic deletions and whole-genome duplication events due, in part, to their far greater fecundity compared with vertebrates.